Carbon Stocks and Transfers in Coniferous Boreal Forests Along a Latitudinal Gradient - Merilä, Päivi; Lindroos, Antti-Jussi; Helmisaari, Heljä-Sisko; Hilli, Sari; Nieminen, Tiina M.; Nöjd, Pekka; Rautio, Pasi; Salemaa, Maija; Ťupek, Boris; Ukonmaanaho, Liisa (Ecosystems)
Correction to: Ecosystems (2024) 27: 151–167 https://doi.org/10.1007/s10021-023-00879-5 In the version of this article initially published, the unit for Fluxes of Dissolved Organic Carbon (DOC g ha−1 year−1) in Bulk Deposition and Throughfall and in Percolation Water at Soil Depths of 5, 20 and 40 cm presented in Table 4 is incorrect. The correct unit is DOC 100 g ha−1 year−1. The same error is in Supplementary file2 (XLSX 19 KB) Abstract Carbon (C) sequestrated in the boreal forest ecosystems plays an important role in climate regulation. This study’s objectives were to quantify the differences in the components of the forest C cycle along a 1000 km latitudinal gradient within the boreal region and between dominant coniferous species in Fennoscandia. The study included seven xeric–sub-xeric and eight mesic–herb-rich heath forests dominated by Scots pine and Norway spruce, respectively. The total site carbon stock (CS) ranged from 81 to 260 Mg ha−1. The largest ecosystem component CSs were tree stems, mineral soil, and humus layer, representing 30 ± 2%, 28 ± 2%, and 13 ± 1% of total CS, respectively. On average, the spruce sites had 40% more C than the pine sites, and CS stored in most compartments was higher on spruce than on pine sites. As exceptions, understorey vegetation and litter layer had a larger CS on pine than on spruce sites. The northern sites had an average of 58% less C than the southern sites. Humus layer CS was the only compartment showing no latitudinal trends. Northern sites had a significantly larger fine and small root CS and understorey CS than southern sites. Most CS compartments were significantly correlated with litterfall C transfer components. Dissolved organic carbon (DOC) flux in throughfall was positively correlated with the aboveground tree compartment CS. Our study revealed patterns of C distribution in major boreal forest ecosystems along latitudinal and fertility gradients, which may serve as a reference for Earth system models and in the evaluation of their projections. 2023